Pengaruh penambahan buah jambu mete (Anacardium occidentale) dan isolat protein kedelai terhadap sifat organoleptik, angka lempeng total dan umur simpan daging analog - Ika Dyah Kumalasari; Annisa Suci Amaliya Rohman (AGROINTEK, 2022)
Meat analogue is a product made from vegetable protein, but conforms to or is similar to the properties of real meat. The quality of a food is determined by its physical, sensory quality, and chemistry including nutritional value and microbiology. The purpose of this study was to determine the acceptability and preference level of organoleptic properties, total plate number and the estimated shelf life of analog meat. The study used five %w/w ratios of cashew fruit: Isolated soy protein: white oyster mushroom, namely F1 (60%:20%:20%); F2 (50%:30%:20%); F3 (40%;40%:20%); F4 (30%:50%:20%); and F5 (20%:60%:20%). The study was conducted in five stages, namely the process of making analog meat, testing product acceptability (scoring), testing organoleptic properties, testing total plate count, and estimating shelf life product. The results of the test on the difference in the treatment of the addition of cashew fruit and ISP affect the acceptability of analog meat. The organoleptic test on the level of preference had a significant effect (p 0.05) on the color, scent, taste, texture, and overall preference of analog meat. The most preferred analog meat color is F1, while the aroma, taste, texture, and overall preference for analog meat are F2. The ALT values of analog meat F1, F2, F3, F4, and F5 that were tested still met the requirements set by BPOM Number 13 of 2019. Analog meat stored at room temperature (20-25˚C) only lasted 2 days, while in cold storage (15-18˚C) can still last for 7 days. Cashew fruit meat has the potential to be developed into analog meat substitutes for animal meat that is organoleptically accepted and meets food safety criteria.